The structure and transcription of an element interspersed between tandem arrays of mini-exon donor RNA genes in Trypanosoma brucei. - Carrington, M (1987)
Messenger RNAs in Trypanosoma brucei brucei have the same 35 bases at the 5' end. These 35 bases are not encoded contiguously in the genome, but are donated from a 140 base RNA (the mini-exon donor RNA). The mini-exon donor RNA (medRNA) is encoded by 1.35 kbp genes that occur in tandem repeats. A DNA element that is associated with mini-exon donor RNA medRNA genes has been identified and characterised by restriction enzyme mapping and partial sequencing. This element (the medRNA gene associated element: MAE) varies in length between 5.5 and 7 kbp. There are between 20 and 40 copies of the element per haploid genome. In clones of genomic DNA MAEs occurred between two medRNA gene arrays and on both sides of a medRNA gene array. The MAEs were always in the same orientation with respect to the medRNA genes. It is proposed that in the genome MAEs are interspersed between tandem arrays of medRNA genes. The transcription of the element has been investigated. Low levels of a 70-80 base transcript derived from a small part of MAE were detected in steady state RNA. Nuclear run off transcript studies indicated that MAEs were transcribed at high levels and that they possibly contain at least one start and stop of transcription.